Factorial Study of Consumer Satisfaction Scale on Indian Telecom Services - Karthikeyan, S (PYC Nepal Journal of Management, 2011)
The article has made an attempt to develop a comprehensive scale for measuring the factors of consumer satisfaction on telecom services in India. A sample of 75 respondents was randomly selected and administered 25-items of consumer satisfaction scale. Results of the factor analysis show the outcome of 3-factors and they were: service availability, service quality and customer service. The final form of the scale consists of 31-items describing the various factors of consumer satisfaction deleting 4-items. Both face and content validities were found in the scale. The study findings would help marketing managers in their consumer studies and in formulating marketing plans accordingly.